Genetic improvement and related activities. Regional activities. Africa. Great Lakes region - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The Great Lakes Regional Bean Program works with the agricultural research institutions of Burundi, Rwanda, and Zaire. Advanced breeding lines were introduced as potential new var. for the region and/or as sources of resistance to angular leaf spot, anthracnose, Ascochyta leaf spot, halo and BCMV, and the bean fly. Together with locally collected germplasm, the introduced germplasm forms an excellent basis for the var. development programs. Advanced lines from all 3 national programs in the region were evaluated for cooking time, water absorption, and hard seed character. A collaborative project between the U. of Munchen and CIAT investigated the significance of var. mixtures in terms of yield gains to obtain information to develop a strategy for improving var. mixtures. The genotypes which gained most from being planted in mixtures were BAT 1297 and PVMX 1531. On-farm var. trials were carried out in Rwanda and Burundi. Diagnostic surveys and exploratory trials were also conducted in several regions of all 3 countries in the Great Lakes Region to establish on-station and on-farm research priorities. Cultural methods (seed selection and removal of diseased leaves and seedlings) in combination show promise as an effective way to control diseases in var. mixtures. The program in 1986 initiated the following technology development and testing trials: (a) chemical seed treatments for areas with root rot, bean fly, and soil acidity problems; (b) a detailed study on the acceptability of climbing beans in the Central Plateau region; (c) on-station trials testing the integration of soil improvement components such as legume-trees and green manures crops in bean production systems; and (d) techniques to improve farmers' self-seed production. (CIAT)